Differentiation of hypervascular primary hepatic tumors showing hepatobiliary hypointensity on gadoxetic acid-enhanced magnetic resonance imaging - Park, Hyun Jeong; Kim, Young Kon; Min, Ji Hye; Lee, Jisun; Lee, Soon Jin; Lee, Eun Sun; Ahn, Soohyun (Abdominal Radiology, 2019)
Purpose: To determine the imaging features that help differentiate hypervascular primary hepatic tumors showing hepatobiliary hypointensity on gadoxetic acid MRI. Methods: This study comprised 148 patients with pathologically proven hypervascular hepatic tumors who underwent gadoxetic acid MRI. Tumors included 23 atypical focal nodular hyperplasias (FNHs), 11 hepatocellular adenomas (HCAs), 15 neuroendocrine tumors (NETs), 25 intrahepatic cholangiocarcinomas (ICCs), and 74 hepatocellular carcinomas (HCCs). MRIs were analyzed for morphologic features, signal intensity, and enhancement pattern of the tumors to determine the differential features using multivariate logistic regression analysis. We evaluated the diagnostic performance of the MRI features for differentiating the five tumor types upon review by two observers. Results: Multivariate analysis revealed that reverse target sign on hepatobiliary phase in FNHs (p = 0.009), iso or hyperintensity on ADC map in FNHs and HCAs (p = 0.009, < 0.001, respectively), central hypointensity on arterial phase in NETs (p = 0.001), hepatobiliary target sign in ICCs (p = 0.002), the presence of septum and capsule in HCCs (all p < 0.001) were significant independent features of each tumor group over other tumor groups. Diagnostic accuracy for both observers was 98–98.6% for FNHs, 96.6–98% for HCAs, 97.3–98.6% for NETs, 90.5–94.6% for ICCs, and 85.8–93.2% for HCCs. Conclusions: Ancillary MRI features established in our study can be helpful in the differentiation of hypervascular and hepatobiliary hypointense primary hepatic tumors on gadoxetic acid MRI.
Keywords: Adult; Aged; Contrast Media; Diagnosis, Differential; Female; Gadolinium DTPA; Humans; Image Enhancement; Liver; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Retrospective Studies; Sensitivity and Specificity; Ancillary feature; Gadoxetic acid; Hypervascular hepatic tumor; MRI